2011
DOI: 10.1113/jphysiol.2010.200345
|View full text |Cite
|
Sign up to set email alerts
|

Unperturbed islet α‐cell function examined in mouse pancreas tissue slices

Abstract: Non-technical summary Critical investigation into pancreatic islet α-cell biology in health and diabetes has been sparse and inconsistent because of technical difficulties in islet isolation and dispersion into single cells. We have circumvented these difficulties by employing the pancreas slice preparation. We functionally characterized (electrophysiologically) the α-cells in their in situ native state, then loaded the tested cells with biocytin dye to subsequently confirm the cell identities by immunocytoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 57 publications
5
77
0
Order By: Relevance
“…One could argue that this is due to compensatory up-regulation of other (less Zn 2+ sensitive) α-cell VGCCs. However, recent large scale patch clamp analysis of identified mouse α-cells in a pancreatic slice preparation indicates that there is actually a wide range of electrophysiological properties due to heterogeneous α-cell ion channel arrangement [36]. Thus, insufficient or biased α-cell sampling could also explain the apparently unchanged whole-cell Ca 2+ current as well as other inconsistencies in the reported ion channel arrangement of mouse α-cells.…”
Section: Role Of Ca V 23 Channels For (Suppression Of) α-Cell Glucagmentioning
confidence: 97%
See 1 more Smart Citation
“…One could argue that this is due to compensatory up-regulation of other (less Zn 2+ sensitive) α-cell VGCCs. However, recent large scale patch clamp analysis of identified mouse α-cells in a pancreatic slice preparation indicates that there is actually a wide range of electrophysiological properties due to heterogeneous α-cell ion channel arrangement [36]. Thus, insufficient or biased α-cell sampling could also explain the apparently unchanged whole-cell Ca 2+ current as well as other inconsistencies in the reported ion channel arrangement of mouse α-cells.…”
Section: Role Of Ca V 23 Channels For (Suppression Of) α-Cell Glucagmentioning
confidence: 97%
“…Due to their intermediate voltage-range for activation Ca v 2.3 channels have been proposed to provide sufficient depolarization after K ATP channel closure for subsequent Na + -and L-type Ca 2+ channel-dependent AP firing [33]. This might be especially important in mouse α-cells, which have very low K ATP channel densities [35,36]. The particular importance of Ca v 2.3 channels for suppressing glucagon release during hyperglycemia could be explained by the fact that high glucose concentrations can directly affect α-cell oxidative metabolism and thereby close K ATP channels [35,37], which has led to the proposal that K ATP channel dependent α-cell depolarization may actually prevent secretion by inactivating Na + and Ca 2+ channels [34,35,37].…”
Section: Role Of Ca V 23 Channels For (Suppression Of) α-Cell Glucagmentioning
confidence: 99%
“…This kind of comparison should however be taken with care because the results were obtained by different groups with different experimental conditions and a limited number of cells. Indeed, a more recent study performed on a larger number of α-cells in mouse pancreatic slices has reported that the density of the K ATP channels was extremely variable between α-cells and in average slightly lower than that of β-cells (Huang et al 2011b). In the mouse, the sensitivity of the K ATP channels to ATP is higher in α-than β-cells (Huang et al 2011b;Leung et al 2006a), whereas in the rat, it is similar in both cell types (Gromada et al 2007).…”
Section: K Atp Channelsmentioning
confidence: 97%
“…Nevertheless, hormone release measurements using the P/Q-type Ca 2+ channel inhibitor ω-agatoxin 1 indicate that the P/Q-type Ca 2+ channels are particularly important for glucagon secretion evoked by low glucose concentrations [26]. In addition, mouse alpha cells express low-threshold T-type Ca 2+ channels that may be involved in the initiation ('pace-making') of action potential firing [47,48].…”
Section: Ion Channels and Islet Cell Electrical Activitymentioning
confidence: 99%